Ratio analysis for decision making, a study - Das, Pradip Kumar (Brazilian Journal of Science, 2023)
Financial statements contemplate to feed financial information in summarized form of a business enterprise to consummate the exigencies of the decision-makers. Veridicality about the causatum and the financial substance of a business belied in statements bide mystic. To decipher peachy godsend and further facilitate the users make well-informed decisions, financial statements necessitate analysis, comparison, and interpretation with ratios. This paper bottomed on secondary data for the stage from 2017-2018 to 2021-2022 encompasses the application of accounting ratios for forging business decision taking Tata Steel Ltd. as the case study. This study unbosoms that the apposite financial information quested for making decision can be documented through the appliance of financial ratio analysis. Thus, management must substantiate that revelation of panoptic financial ratios outline basic financial statement drafted for the plenary perception of business enterprises.